This is your brain on stereotypes : how science is tackling unconscious bias - Kyi, Tanya Lloyd, 1973- (Kids Can Press, 2020)
Explores the science behind stereotypes, discussing how our brains form them to recognizing them and how that can make us less biased. Explains the history of identifying and studying stereotypes, secret biases, how stereotypes affect a sense of self, and how science can help humans overcome their biases. Includes sidebars and resources for further information.